Does Cognitive Dysfunction in Bipolar Disorder Qualify as a Diagnostic Intermediate Phenotype?—A Perspective Paper - Kessing, Lars Vedel; Miskowiak, Kamilla (Frontiers in Psychiatry, 2018)
The present perspective paper addresses and discusses whether cognitive dysfunction in bipolar disorder qualifies as a diagnostic intermediate phenotype using the Robin and Guzé criteria of diagnostic validity (1). The paper reviews current data within 1) delineation of the clinical intermediate phenotype, 2) associations of the intermediate phenotype with para-clinical data such as brain imaging and blood based data, 3) associations to family history / genetics, 4) characteristics during long-term follow-up and 5) treatment effects on cognition. In this way, the paper identifies knowledge gaps and suggests recommendations for future research within each of the five areas. Based on the current state of knowledge, we conclude that cognitive dysfunction does not qualify as a diagnostic intermediate phenotype or endophenotype for bipolar disorder, although promising new evidence points to emotion and reward processing abnormalities as possible putative endophenotypes.